WELLNESS RESORT DESIGN WITH BIOPHILIC APPROACH IN CIATER - Ayu Lestari, Tidi
Physical and mental health issues have a very close relationship with lifestyle choices. A bad lifestyle has a negative impact on physical, and mental health. A person can be said to be healthy if fulfills a balance in three aspects, physical, mental and social. Wellness lifestyle is used as an effort to improve the quality of health with a wellness resort as a facility to find a lifestyle that suits each person. To design a facility for a wellness lifestyle, the biophilic approach is used because biophilic emphasizes the connection between humans and nature to achieve a healthy quality mind-body system, cognitive, physiological and psychological. Site context (place-based), wellness program, and biophilic patterns are aspects that cannot be separated in the design process. The purpose of designing Sariater Wellness Resort is to optimize the design of the resort building that can improve the quality of physical, and psychological health (mind-body system) by reducing stress, increasing cognitive performance, and generating emotion, mood and preference.